2019
DOI: 10.1044/2018_jslhr-h-18-0273
|View full text |Cite
|
Sign up to set email alerts
|

Sentence Context Facilitation for Children's and Adults' Recognition of Native- and Nonnative-Accented Speech

Abstract: Supportive semantic and syntactic information can increase children's and adults' word recognition accuracy in adverse listening conditions. However, there are inconsistent findings regarding how a talker's accent or dialect modulates these context effects. Here, we compare children's and adults' abilities to capitalize on sentence context to overcome misleading acousticphonetic cues in nonnative-accented speech. Method: Monolingual American English speaking 5-to 7-year-old children (n = 90) and 18-to 35-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…The importance of co-textual and contextual information for linguistic comprehension is generally acknowledged by researchers: It is well established that both L1 and L2 listening are cognitively interactive processes in which listeners combine information from the acoustic signal with information from linguistic co-text and extralinguistic context (e.g., Field 2004Field , 2008Goh & Vandergrift, 2021; see also Kennedy, 2021). This has repeatedly been demonstrated regarding intelligibility to L1 listeners in publications on speech science, psycholinguistics, or speech pathology (e.g., Bent et al, 2019;Garcia & Cannito, 1996;Kamide et al, 2003) and regarding L2 listening comprehension more generally (e.g., Macaro et al, 2005). However, research on co-textual and contextual effects has been comparatively scarce concerning intelligibility to L2 listeners, notably L2 listeners in lingua franca (LF) listening situations-that is, when listening to another nonnative accent.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The importance of co-textual and contextual information for linguistic comprehension is generally acknowledged by researchers: It is well established that both L1 and L2 listening are cognitively interactive processes in which listeners combine information from the acoustic signal with information from linguistic co-text and extralinguistic context (e.g., Field 2004Field , 2008Goh & Vandergrift, 2021; see also Kennedy, 2021). This has repeatedly been demonstrated regarding intelligibility to L1 listeners in publications on speech science, psycholinguistics, or speech pathology (e.g., Bent et al, 2019;Garcia & Cannito, 1996;Kamide et al, 2003) and regarding L2 listening comprehension more generally (e.g., Macaro et al, 2005). However, research on co-textual and contextual effects has been comparatively scarce concerning intelligibility to L2 listeners, notably L2 listeners in lingua franca (LF) listening situations-that is, when listening to another nonnative accent.…”
Section: Introductionmentioning
confidence: 95%
“…Studies have shown that listeners draw on lexical knowledge—for example word frequency knowledge or knowledge of the phonological “neighborhood” of a word (Bradlow & Pisoni, 1999; Luce & Pisoni, 1998)—and on aspects of the visual context, such as gestures (Garcia & Cannito, 1996) or referent availability (Tanenhaus et al, 1995), to identify spoken words. Additionally, numerous studies have provided evidence for the use of sentence co-text in SWR, with syntactic, semantic, and collocational constraints aiding listeners in recognizing words (Baese-Berk et al, 2021; Behrman & Akhund, 2013; Bent et al, 2019; Hilpert, 2008; Kennedy & Trofimovich, 2008). Sentence co-text has also been found to facilitate SWR by triggering certain schematic expectations that make listeners anticipate the intended word (Kamide et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Listeners often have more difficulty understanding L2-accented speech than L1-accented speech (though this depends on speaker fluency; Munro & Derwing, 1995), and individual listener differences in cognitive ability, such as working memory capacity (McLaughlin, Baese-Berk, Bent, Borrie, & Van Engen, 2018) and vocabulary knowledge (Banks, Gowen, Munro, & Adank, 2015;Bent, Holt, Miller, & Libersky, 2019;McLaughlin et al, 2018), account for some variation among listeners. Additionally, while it may be cognitively demanding to process an L2 accent initially , listeners can rapidly adapt to unfamiliar L2accented speech (Clarke & Garrett, 2004;Bradlow & Bent, 2008), thereby reducing the cognitive demands of speech processing (Brown, McLaughlin, Strand, & Van Engen, 2020).…”
Section: Introductionmentioning
confidence: 99%